Corporate governance index in emerging markets: Peruvian listed companies (2016)
Companies are wishing to incorporate good corporate governance practices into their organization in order to be more attractive to investors, knowing whether this influences their financial indicators and profitability or not. This, in fact, is beneficial for investors so they know that a company who applies the principles of corporate governance (CG) presents best management practices and transparent information, safeguarding the interests of all its stakeholders, which helps their investment decision; reducing market uncertainty, making it more efficient and liquid. The research focuses on the companies listed in the Stock Exchange of Lima that had implemented CG strategies in their organizations